Extraction of Geospatial Information from Open-Source data platforms for Urban Environment Analysis of health-influencing urban indicators - case study Bratislava Petržalka - Šimkovičová, Barbora; Smatanová, Katarína; Chen, Congsyuan (ECON Publishing, 2025)
This study examines whether freely available open-source geospatial data can be used to calculate urban indicators that affect public health and environmental sustainability. The main aim is to assess the availability, structure, and resolution of such datasets in the Slovak context, using the Petržalka district of Bratislava as a case study. The methodology includes the use of desk research and GIS-based analysis to identify suitable indicators and calculate their values. Key findings highlight limitations in data granularity and consistency across platforms but also confirm that several indicators - such as tree canopy cover, built-up area density, and access to green spaces – can be extracted. The results underline the urgent need for better access to geospatial data infrastructure in Slovakia and support the potential use of open-source data in developing future composite indicators.
Keywords: Urban planning; geospatial analysis; health-influencing urban indicators; public health; urban design